Treatment with the mitochondrial‐targeted antioxidant peptide SS‐31 rescues neurovascular coupling responses and cerebrovascular endothelial function and improves cognition in aged mice. Issue 2 (6th February 2018) - Tarantini, Stefano; Valcarcel‐Ares, Noa M.; Yabluchanskiy, Andriy; Fulop, Gabor A.; Hertelendy, Peter; Gautam, Tripti; Farkas, Eszter; Perz, Aleksandra; Rabinovitch, Peter S.; Sonntag, William E.; Csiszar, Anna; Ungvari, Zoltan
Summary: Moment‐to‐moment adjustment of cerebral blood flow (CBF) via neurovascular coupling has an essential role in maintenance of healthy cognitive function. In advanced age, increased oxidative stress and cerebromicrovascular endothelial dysfunction impair neurovascular coupling, likely contributing to age‐related decline of higher cortical functions. There is increasing evidence showing that mitochondrial oxidative stress plays a critical role in a range of age‐related cellular impairments, but its role in neurovascular uncoupling remains unexplored. This study was designed to test the hypothesis that attenuation of mitochondrial oxidative stress may exert beneficial effects on neurovascular coupling responses in aging. To test this hypothesis, 24‐month‐old C57BL/6 mice were treated with a cell‐permeable, mitochondria‐targeted antioxidant peptide (SS‐31; 10 mg kg −1 day −1, i.p.) or vehicle for 2 weeks. Neurovascular coupling was assessed by measuring CBF responses (laser speckle contrast imaging) evoked by contralateral whisker stimulation. We found that neurovascular coupling responses were significantly impaired in aged mice. Treatment with SS–31 significantly improved neurovascular coupling responses by increasing NO‐mediated cerebromicrovascular dilation, which was associated with significantly improved spatial working memory, motor skill learning, and gait coordination. These findings are paralleled by the protective effects of SS–31 on mitochondrial production of reactive oxygen species and mitochondrial respiration in cultured cerebromicrovascular endothelial cells derived from aged animals. Thus, mitochondrial oxidative stress contributes to age‐related cerebromicrovascular dysfunction, exacerbating cognitive decline. We propose that mitochondria‐targeted antioxidants may be considered for pharmacological microvascular protection for the prevention/treatment of age‐related vascular cognitive impairment (VCI).